Langerhans Cell Histiocytosis of the Head and Neck: Experience at a Rural Tertiary Referral Center. (April 2023) - Schwartz, Tyler R.; Elliott, Leighton A.; Fenley, Heather; Ramdas, Jagadeesh; Scott Greene, Joseph
Objectives: Retrospectively analyze head and neck Langerhans Cell Histiocytosis at a rural tertiary referral center and compare results with previously published data. Methods: Electronic health record review was performed from 2003 to 2019. Patients with biopsy proven LCH with primary head and neck involvement were included. Demographics, presentation, imaging characteristics, treatment modality, delay in diagnosis (DD, ≥60 days), and outcomes were analyzed and reported. Results: Twenty-four patients were included. The most common presenting symptoms were otorrhea (n = 6) and scalp pain or swelling (n = 6). All patients had bony involvement. The most common site was facial or skull lesions (n = 20). Most skull lesions (75%) demonstrated CNS risk. Six patients were treated with primary surgery, 15 with primary chemotherapy, and 3 with surgery plus adjuvant chemotherapy. Nine patients experienced relapse of disease with median time to documented relapse of 11.4 months; all were treated with salvage chemotherapy to achieve complete remission (median follow-up: 72 months). Patients most likely to relapse were those with multisystem disease (5/7, 71.4%), temporal bone lesions (4/7, 57.1%), and DD (7/12, 58.3%). Of the 9 total patients who experienced relapse, 78% had a delay in diagnosis. Conclusions: LCH is a complex disease process in which diagnosis can be delayed if not considered in the differential. Within the head and neck, the skull, including isolated temporal bone involvement, is the most common site of involvement. Treatment modality does not appear to have an influence on relapse rates. Relapse was more likely to occur in the first year after treatment and close monitoring is required.